PANCASILA SEBAGAI LANDASAN ILMU POLITIK - Romandes, Muhammad Hafizt (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Pancasila as the basis of the Indonesian state has an important role in the development of political science in Indonesia. This article aims to analyze how Pancasila functions as a foundation for political science, as well as its implications for the government system and national life. The method used in this research is qualitative analysis with a literature study approach and a review of related laws and regulations. The research results show that Pancasila values provide direction and foundation for political practice in Indonesia, as well as strengthening national identity and national unity.